Prediction of Target Motion Drives Oculomotor Response during Target Occlusions - Zemblys, R.; Laurutis, V. (Elektronika ir Elektrotechnika, 2012)
Prediction of object motion allows overcoming of object occlusions in its trajectory. In this study pseudorandom target trajectory with occlusions of 500 ms was used. It was found that for a period up to 200 ms after target occlusion, oculomotor system was driven by a short-term memory of the pre-occlusion target motion trajectory. We conclude, that when visual system is no longer able to predict location of occluded target, there is a tendency to shift gaze away from previous target location, similarly, away from the edges of the screen. We suggest that this is due to probability, accumulated in long-term memory, which supports expectation that the target should reappear near the centre of the screen. This behaviour supports basic principles of Bayesian decision theory. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2807